2014
DOI: 10.1021/cg5005165
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Superconductivity, and Magnetism of Ce(O,F)BiS2 Single Crystals

Abstract: The crystal structures of Ce(O,F)BiS 2 synthesized from starting materials with five different F contents were determined by single-crystal X-ray analysis. An increase in F content in the starting materials slightly increased F incorporation in the grown single crystals. The grown crystals with various F contents showed similar layered structures, but minor structural changes were observed with different conductive and magnetic properties. Crystals grown from higher F content were found to have a nearly flat B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 39 publications
7
47
0
Order By: Relevance
“…The nominal composition of F was set to be x = 0.7. Details on the sample preparation and characterization are given elsewhere [18,19,21,24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nominal composition of F was set to be x = 0.7. Details on the sample preparation and characterization are given elsewhere [18,19,21,24].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is concluded that the superconducting and the magnetically ordered states coexist for higher x at low temperatures [12][13][14][15]. These findings have caused particular interest in this compound and stimulated further investigations of it [16][17][18][19][20][21][22][23]. The phase diagrams, obtained by systematic investigation for nominal F-concentration (x) dependence (x = 0.0-1.0) of both the magnetic ordering and the superconducting properties of the as-grown polycrystalline samples, show that ferromagnetic-like ordering occurs at slightly higher temperature than the superconducting transition for x > 0.4 [21].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, two types of magnetic ordering and superconductivity are observed in single crystals of CeO 1−x FxBiS 2 [70]. Figure 13 shows the temperature dependence of the magnetization for single crystals of CeO 1−x FxBiS 2 .…”
Section: Coexistence Of Superconductivity and Magnetismmentioning
confidence: 99%
“…The other subfamily, which branched out of research on La(O,F)BiS 2 , has been studied extensively. Magnetic order and charge density wave order have been found, both theoretically and experimentally [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%